Better to wish - Martin, Ann M., 1955- (Martin, Ann M., 1955- Family tree, 2013)
In 1930 Abby Nichols is an eight-year-old girl growing up in Maine, but as the Depression deepens, and her mother dies, the responsibility of taking care of her family falls to her, and she has to put her dreams of going to college and becoming a writer on hold.